2021
DOI: 10.18632/aging.202828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel functional CpG-SNPs associated with Type 2 diabetes and birth weight

Abstract: Genome-wide association studies (GWASs) have identified hundreds of genetic loci for type 2 diabetes (T2D) and birth weight (BW); however, a large proportion of the total trait heritability remains unexplained. The previous studies were generally focused on individual traits and largely failed to identify the majority of the variants that play key functional roles in the etiology of the disease. Here, we aim to identify novel functional loci for T2D, BW and the pleiotropic variants shared between them by perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…[ 65 ] Besides, multiple shared CpG-SNPs of type 2 diabetes risk and birth weight are methylation QTL (me-QTL), metabolic QTL (meta-QTL), or e-QTL. [ 66 ] Our GTEX analysis with the public database showed that CD80 mRNA expression was increased with the number of rs34394661A allele in 9 tissues, which supports the possible tissue-wide influence of the SNP on both CD80_ cg06300880 methylation and CD80 transcriptional activity.…”
Section: Discussionsupporting
confidence: 64%
“…[ 65 ] Besides, multiple shared CpG-SNPs of type 2 diabetes risk and birth weight are methylation QTL (me-QTL), metabolic QTL (meta-QTL), or e-QTL. [ 66 ] Our GTEX analysis with the public database showed that CD80 mRNA expression was increased with the number of rs34394661A allele in 9 tissues, which supports the possible tissue-wide influence of the SNP on both CD80_ cg06300880 methylation and CD80 transcriptional activity.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, rs947591 was associated with other traits, including triglyceride and total cholesterol levels in the Chinese population [46]. rs2488071 was identified as a novel functional locus shared between T2D and birth weight in Chinese populations [47]. It seems that rs947591 is an important genetic variant that requires replication in different ethnic populations as biomarkers for the risk of T2D.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation can also be altered as a result of genetic variants: epigenome-wide approaches on human islets have identified hypo- and hyper-methylated regions in T2D, some of these mapping to GWAS loci such as ADYC5 or KCNQ1 [ 316 , 317 ]. T2D-risk SNPs at potential sites of methylation (CpG dinucleotides) have also been mapped [ 318 , 319 ]. There are other underexplored DNA modifications such as 5-hydroxymethylcytosine (5hmC) that have an impact in chromatin architecture and gene expression.…”
Section: Classification Of the Genetic Drivers Of β Cell Dysfunctionmentioning
confidence: 99%